2006
DOI: 10.1038/sj.ki.5000307
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of baroreflex function in juvenile end-stage renal disease

Abstract: Arterial baroreflex sensitivity (BRS) is markedly reduced in middle-aged patients with end-stage renal disease (ESRD), due to the combined effects of aging, arterial stiffening, and autonomic neuropathy. Much less is known about the effects of ESRD on arterial baroreflex in juvenile patients. Therefore, we investigated baroreflex function and its relation to carotid artery elasticity and heart rate variability in children and young adults with ESRD. We studied 42 subjects (9-30 years): 14 patients on maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…The inability to transduce BP changes to the brain, as recently shown in our CKD model in which impaired baroreceptor afferent function correlated with vascular remodeling in the aortic arch [13••], then is associated with defective baroreflex control of autonomic outflows and altered tonic levels of sympathetic and vagal efferent activity. Indeed, studies have shown a negative association between BRS and the magnitude of vascular calcification [97,101] and arterial stiffness [70] in chronic hemodialysis patients. In renal transplant patients, increased levels of muscle SNA were correlated with impaired arterial distensibility [102].…”
Section: Cardiovascular Remodeling In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…The inability to transduce BP changes to the brain, as recently shown in our CKD model in which impaired baroreceptor afferent function correlated with vascular remodeling in the aortic arch [13••], then is associated with defective baroreflex control of autonomic outflows and altered tonic levels of sympathetic and vagal efferent activity. Indeed, studies have shown a negative association between BRS and the magnitude of vascular calcification [97,101] and arterial stiffness [70] in chronic hemodialysis patients. In renal transplant patients, increased levels of muscle SNA were correlated with impaired arterial distensibility [102].…”
Section: Cardiovascular Remodeling In Ckdmentioning
confidence: 99%
“…In clinical practice, prognostic information on cardiovascular morbidity and mortality in CKD may be derived by (1) measuring cardiac BRS, an independent predictor of sudden cardiac death accompanying CKD [24], and (2) using the baroreflex effectiveness index (BEI), a measure of the number of times baroreflex is active in controlling HR in response to BP fluctuations [67]; both tools are recognized as strong independent predictors of long-term survival in the CKD population [24]. Indeed, HR BRS, either spontaneous [24,[68][69][70] or evoked by pharmacologic manipulation of BP [31,65,70], and BEI [24] are reduced in CKD, and, most importantly, deficits correlate with reductions in the GFR [69], suggesting a direct association between deterioration in renal function and alterations in the cardiac baroreflex mechanism, rendering these markers useful in assessing cardiovascular risk in CKD.…”
Section: Altered Reflex Control Mechanisms Of Autonomic Outflows In Ckdmentioning
confidence: 99%
“…In dialysis patients, significant reduction in activity in both systems has been reported. 35,36 In diabetic patients without renal failure, pronounced derangement has been noted as strongly related to metabolic control. 37-39 R-R variability as an index of autonomic neuropathy was found associated with LVM in diabetic patients on hemodialysis, 40 41 It was hypothesized that an accumulation of icodextrin metabolites in the bloodstream exerts an osmotic effect, which increases the blood volume and, secondarily, BP and NT-pro-BNT.…”
Section: S126mentioning
confidence: 99%
“…While these changes appear in the early stages of CKD, they are more pronounced in advanced stages. In CKD, poorly controlled (especially systolic) hypertension is associated with advanced arteriosclerosis, rigid arteries, impaired baroreflex sensitivity and autonomic dysfunction, creating a vicious cycle [41,42] . Additionally, in ESRD, the synergism between hyperphosphatemia, calcitriol, calcium carbonate, warfarin, hypertension and atherosclerosis provides the perfect breeding ground for vascular calcification [15,38] .…”
Section: Pwv: Pathophysiological Integration and Basis For Early Intementioning
confidence: 99%